Results of the surgical treatment of esophageal cancer - Rubio, Roberto; Müller, Günther (Cirugía del Uruguay, 1975)
19 caneers oi the middle (11) and lOwet (8) lhlrds oi lhe esophagus were treated by eS"ophagecwmy ,vi1.h proximal-ga trectomy (17 cases) or witb total gastreetorny (2 cases). In only one patient pre-operfltive irradifltion was performed, Surgery was considered almingly curative In 8 cases nnd surely palllative In thc other 11 cases. Continuity was reS'tored by lntrathoracie esophago-gastrostomy in 17 cases, snd by esOphe.gojejunal anastomOsis in the other 2. Sura:ical mortality was 10,5 %, that is. 2 Piltients. One oi them -the only one radlated-died due to disruption o[ the esophagogas"tric anastomosis. TIte average oí post-operative survivaL was 15 months.